Sexually dimorphic pubertal development and adipose tissue kisspeptin dysregulation in the obese and preeclamptic-like BPH/5 mouse model offspring - Gomes, Viviane C. L.; Beckers, Kalie F.; Crissman, Kassandra R.; Landry, Camille A.; Flanagan, Juliet P.; Awad, Reham M.; Piero, Fabio Del; Liu, Chin-Chi; Sones, Jenny L. (Frontiers in Physiology, 2023)
Preeclampsia (PE) is a devastating hypertensive disorder of pregnancy closely linked to obesity. Long-term adverse outcomes may occur in offspring from preeclamptic pregnancies. Accordingly, sex-specific changes in pubertal development have been described in children from preeclamptic women, but the underlying mechanisms remain vastly unexplored. Features of PE are spontaneously recapitulated by the blood pressure high subline 5 (BPH/5) mouse model, including obesity, and dyslipidemia in females before and throughout pregnancy, superimposed hypertension from late gestation to parturition and fetal growth restriction. A sexually dimorphic cardiometabolic phenotype has been described in BPH/5 offspring: while females are hyperphagic, hyperleptinemic, and overweight, with increased reproductive white adipose tissue (rWAT), males have similar food intake, serum leptin concentration, body weight (BW) and rWAT mass as controls. Herein, pubertal development and the influence of adiposity were investigated in BPH/5 progeny. Precocious onset of puberty occurs in BPH/5 females, but not in male offspring. Nonetheless, both BPH/5 males and females display abnormal reproductive features during early adulthood, including hypoestrogenism and hyperandrogenism in females and increased testicular weight in males. Kisspeptins, a family of peptides closely linked to reproduction and metabolism, have been previously shown to inhibit adipogenesis. Interestingly, expression of kisspeptins (Kiss1) and their cognate receptor (Kiss1r) in the adipose tissue seem to be modulated by the sex steroid hormone milieu. To further understand the metabolic-reproductive crosstalk in the BPH/5 offspring, Kiss1/Kiss1r expression in male and female rWAT were investigated. Downregulation of Kiss1/Kiss1r occurs in BPH/5 females, but not in males. Interestingly, pair feeding BPH/5 females attenuated circulating testosterone concentration and rWAT Kiss1 downregulation. Altogether, the studies demonstrate reproductive abnormalities in offspring gestated in a PE-like uterus, which appear to be closely associated to the sexually dimorphic metabolic phenotype of the BPH/5 mouse model.